As responsabilidades legais dos auditores independentes no Brasil e seu monitoramento perante os órgãos reguladores - Campelo, Aldeir de Lima (2010)
The independent audit activity can exclusively be performed by accountants who conduct the investigation of the financial statements of listed companies, as well as large companies, as defined by article 3º of Law 11.638/2007, even if such large companies are not listed. In order to exercise such activity the accountants are required to be registered in the Brazilian Securities and Exchange Commission as well as in the Regional Accounting Council of their jurisdiction. All professional activities require involvement, commitment and mainly responsibility in its practice and such responsibility may vary according to the implications from their work. Independent auditors also follow this rule and due to the relevance of their services, must be totally reliable. Based on these aspects, the goal of this study is mainly to identify the legal responsibilities of independent auditors in Brazil through the verification if such liabilities are being monitored by regulators and how this monitoring is performed. Therefore, the study presents the development of independent audit activity in Brazil, the conceptual aspects, genres, as well as financial statements, generally accepted auditing standards and professional standards. This is a study with a methodology based on the review of theoretical literature and also in research of the explanatory-descriptive. Regulators presented in the research are the Federal Accounting Council, the Brazilian Securities and Exchange Commission and the Brazilian Central Bank. These three regulatory agencies have designated a person to answer the questionnaire prepared for this purpose, with open questions. The responses of the regulators, in conjunction with the theory study, since the initial development to the results, present a study that meets its objective, and provides credibility to the reader